The archaeology of eastern Lutruwita (Tasmania) - Richard Cosgrove; John Webb; Jillian Garvey; Jeff Theys; Rhys Jones (Archaeology in Oceania, 2024)
Fifty years have passed since the first systematic archaeological surveys and excavations were conducted in Lutruwita (Tasmania). Despite numerous Late Pleistocene archaeological discoveries in the southwest region, no indisputable pre-Holocene sites have been found in eastern Tasmania. This profound difference raises questions about how Aboriginal people utilised the Lutruwita landscape; first as a projecting peninsula into the Southern Ocean and then as an island cut off by rising seas c.14000 years ago. To examine the difference between east and west further, legacy data excavated by one of us (RJ) in 1964 at the Oatlands OL1 site and stored at the Tasmanian Museum and Art Gallery (TMAG) has been analysed. The results of pXRF chemical analysis of artefact raw material, radiocarbon dating and studies of faunal remains have produced information that highlights the Holocene interaction between people in eastern Lutruwita. Despite the current lack of Late Pleistocene evidence from eastern Lutruwita, this pattern appears to be different from land use models for Late Pleistocene southwestern Lutruwita. With new information from the OL1 rock shelter site we can now contrast the Late Pleistocene hunting economics with the exceptionally well-preserved faunal remains found in the Holocene site, OL1.